Photoassociation dynamics driven by second- and third-order phase-modulated laser fields. (11th April 2016) - Wang, Meng; Chen, Mao-Du; Hu, Xue-Jin; Li, Jing-Lun; Cong, Shu-Lin
Abstract: We investigate theoretically the photoassociation dynamics of ultracold 85 Rb atoms driven by second- and third-order phase-modulated laser fields. The interplay between the second-order and third-order terms of the phase-modulated pulse has an obvious influence on photoassociation dynamics. The different combinations of the second-order and third-order phase coefficients lead to different pulse shapes. Most of the molecular population in the excited electronic state driven only by the third-order phase pulses can be distributed in a single vibrational level. The second-order term of the phase-modulated pulse can change the instantaneous frequency, and therefore the final population is distributed on several resonant vibrational levels, instead of concentrating on a single level. Although the second- and third-order phase-modulated pulse covers more resonant vibrational levels, the total population on the resonant vibrational levels is much smaller than that controlled only by the third-order phase pulse. In particular, the third-order term of the phase-modulated pulse can weaken the 'multiple interaction' to some degree.